Cognitive closure and risk sensitivity in the fear of crime. (5th October 2013) - Jackson, Jonathan
<x xml:space="preserve">Abstract</x> Purpose This study was designed to answer two questions. First, does the risk sensitivity model of worry about crime replicate in three European countries? Second, can the model be extended to include need for cognitive closure? Method A national probability survey in Italy, Bulgaria, and Lithuania measured worry about criminal victimization, risk perception, and need for cognitive closure. Additive and interactive relationships between latent constructs were tested using latent moderated structural equation modelling. Results First, perceived likelihood, control, and consequence were statistically significant additive predictors of worry about crime. Second, the association between subjective probability judgements and worry about crime was stronger among people who associated the uncertain event with serious personal consequences and among people who had a high need for cognitive closure. Third, need for cognitive closure was associated with greater perceived consequences of victimization, but not with different perceptions of the likelihood and controllability of personal victimization. Conclusions This study provides empirical support for an extended risk sensitivity model in three European countries. Findings suggest that risk perception involves multiple – and interacting – dimensions that constitute sensitivity to risk, as well as individual differences in knowledge construction, information judgement, and processing. Future work should address (1) whether probability judgements shift psychological distance to uncertain future outcomes, and (2) whether the effect of psychological distance on worry about crime is greater among people who construe the outcome to be severe in consequence and who desire definite knowledge and dislike uncertainty in their lives.